Late‐Stage Functionalization of Histidine in Unprotected Peptides. (7th November 2019) - Noisier, Anaïs F. M.; Johansson, Magnus J.; Knerr, Laurent; Hayes, Martin A.; Drury, William J.; Valeur, Eric; Malins, Lara R.; Gopalakrishnan, Ranganath
Abstract: The late‐stage functionalization (LSF) of peptides represents a valuable strategy for the design of potent peptide pharmaceuticals by enabling rapid exploration of chemical diversity and offering novel opportunities for peptide conjugation. While the C(sp 2 )−H activation of tryptophan (Trp) is well documented, the resurgence of radical chemistry is opening new avenues for the C−H functionalization of other aromatic side‐chains. Herein, we report the first example of LSF at C2 of histidine (His) utilizing a broad scope of aliphatic sulfinate salts as radical precursors. In this work, the exquisite selectivity for histidine functionalization was demonstrated through the alkylation of complex unprotected peptides in aqueous media. Finally, this methodology was extended for the installation of a ketone handle, providing an unprecedented anchor for selective oxime/hydrazone conjugation at histidine. Abstract : C−H(is)‐Funktionalisierung : Das erste Beispiel einer chemoselektiven C‐2‐Alkylierung Histidin‐haltiger Peptide durch eine milde Minisci‐Reaktion wird vorgestellt. Dieser Ansatz ermöglicht das rasche Ausloten der chemischen Diversität im Umfeld dieses wenig erforschten Restes und eröffnet eine neue Möglichkeit zur Markierung und Konjugation von Peptiden.